2022
DOI: 10.1002/capr.12533
|View full text |Cite
|
Sign up to set email alerts
|

Alienated and unsafe: Experiences of the first national UK COVID‐19 lockdown for vulnerable young people (aged 11–24 years) as revealed in Web‐based therapeutic sessions with mental health professionals

Abstract: Background The COVID‐19 pandemic and subsequent lockdowns have disproportionately affected young people, and those who are vulnerable are disadvantaged further. Here, we seek to understand the experiences of vulnerable young people accessing Web‐based therapeutic support during the pandemic and early lockdown, as revealed through the observations of mental health professionals. Methods Four focus groups with 12 professionals from a digital mental health service were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…We found that service activity changed and increase during the pandemic but changes in the referral sources and the way people access to pathways of care more generally may have impacted the increase in service access and demand, as contacts per users were higher in pre-pandemic activity when compared, our data suggest that dramatic changes in the healthcare system are likely to impact too digital ecosystems of support, even when operating anonymously and with relatively ease of access online, interoperability between services may be important in order to . We also observed changes in the presenting concerns to those likely to impact children and young people during the pandemic 29,30, 31, 32, 33, with considerable increases on risk, self-harm and suicidal ideation, as well as other mental health related difficulties, increasing the difficulties to those more vulnerable 9 . Finally, we observed how contacts by ethnicity and area deprivation levels experienced changes in the rates of increase at the beginning of Covid-19, showing how global traumatic events like a pandemic, may be an opportunity to tackle inequality of service access to mental health support and service access online for children and young people, especially when responses to disasters are due to change these services and its use.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We found that service activity changed and increase during the pandemic but changes in the referral sources and the way people access to pathways of care more generally may have impacted the increase in service access and demand, as contacts per users were higher in pre-pandemic activity when compared, our data suggest that dramatic changes in the healthcare system are likely to impact too digital ecosystems of support, even when operating anonymously and with relatively ease of access online, interoperability between services may be important in order to . We also observed changes in the presenting concerns to those likely to impact children and young people during the pandemic 29,30, 31, 32, 33, with considerable increases on risk, self-harm and suicidal ideation, as well as other mental health related difficulties, increasing the difficulties to those more vulnerable 9 . Finally, we observed how contacts by ethnicity and area deprivation levels experienced changes in the rates of increase at the beginning of Covid-19, showing how global traumatic events like a pandemic, may be an opportunity to tackle inequality of service access to mental health support and service access online for children and young people, especially when responses to disasters are due to change these services and its use.…”
Section: Discussionmentioning
confidence: 77%
“…Issues of risk, abuse and, safeguarding have been a particular concern in the UK throughout the lockdown periods with typical avenues where a child at risk would be identified as being restricted, such as schools 46 or community support. Anonymous and text-based services such as Kooth may have provided vulnerable children and young people at risk a support system replacement at a time when access to standard face-to-face support was restricted, and communication such as telephone and video calls may have been difficult in the confined environment of lockdowns 9 .…”
Section: User's Mental Health Presenting Concernsmentioning
confidence: 99%
“…For example, in the study by Mindel et al (2022), the understanding of the experiences of vulnerable youth in accessing web-based therapeutic support during the COVID-19 pandemic and quarantine was investigated. The results showed that these youths experienced feelings of being unnoticed, insecurity, and lack of community support regarding COVID-19 ( 28 ). In accounting for this finding, it can be said that individuals tend to feel anxious and insecure when the environment changes.…”
Section: Discussionmentioning
confidence: 97%
“…Experiences of the pandemic will have been especially difficult for CYP who have a history of mental/physical health problems or are from disadvantaged backgrounds. Young people accessing digital mental health services, who are already known to be more vulnerable, are at a higher probability of heightened risk, loss of progress, as well as, increased experiences of isolation and will require ongoing psychological support 9 .…”
Section: Introductionmentioning
confidence: 99%